Management and outcomes of sinus histiocytosis with massive lymphadenopathy (Rosai Dorfman Disease). Issue 4 (20th March 2020) - Namoglu, Esin C.; Hughes, Mitchell E.; Plastaras, John P.; Landsburg, Daniel J.; Maity, Amit; Nasta, Sunita D.
Abstract: Sinus histiocytosis with massive lymphadenopathy (Rosai Dorfman Disease [RDD]), is a rare, benign but clinically heterogeneous histiocytic disorder. Our aims were to analyze the clinical characteristics of the disease and explore the outcomes of patients with RDD followed at our institution. Between January 2000 and February 2019, there were 15 patients with a pathologically confirmed diagnosis of RDD. Median age at diagnosis was 48 years old (range 26–78). The majority (87%, n  = 13) of the patients had extranodal disease. Frontline approaches included surgical intervention/complete excision ( n  = 5, 33%), rituximab monotherapy ( n  = 5, 33%), observation ( n  = 3, 20%), and radiation ( n  = 2, 13%). Two of the five patients underwent surgical excision and were subsequently treated with rituximab. Of the 7 patients who were given rituximab, 64% remained progression free 24 months after the initial rituximab administration. Our review parallels previous reports and highlights rituximab as a favorable option for therapy if ineligible for surgery or radiation.